ABORSI BAGI KORBAN PEMERKOSAAN: PERSPEKTIF IMAM SYAFI’I, IMAM MALIKI DAN HUKUM PIDANA INDONESIA - Alif Nurhayati; Rodhi Fata; Salma Khoirun Nisa’; Aprilia Intan Ayu A (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2025)
This paper explores the issue of abortion for rape victims from the perspectives of Imam Shafi'i, Imam Maliki, and Indonesian criminal law. Imam Shafi'i generally prohibits abortion after the soul is believed to enter the fetus, typically at 120 days, but some interpretations allow it before that point under pressing circumstances. Imam Maliki takes a stricter view, opposing abortion at all stages, even before ensoulment. In contrast, Indonesian criminal law permits abortion for rape victims under certain conditions, including a limited gestational age, in accordance with health regulations and the 2009 Health Law. By comparing these perspectives, the study highlights the tension between religious interpretations and legal frameworks in addressing sensitive moral and legal dilemmas faced by rape survivors.